Smokeless Burn Barrel: Solusi pembakaran sampah minim asap di Desa Ledok, Blora - Maria, Joana; Fitri Fathia, Khoyimah; Mahardika, Putri; Muzzazinah, Muzzazinah; Alfi Ramadanu, Pradipta; Nuraini Dewi, Arifah; Handayani, Aulia; Feillysita Marsha, Chacha; Oktorino Putra Purnama, Daffa; Hanifah, Asma’ (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Waste burning smoke is very dangerous for the health of living things, so this needs to be minimized in order to maintain a healthy environment. Smokeless Burn Barrel is a simple tool specifically designed to minimize the smoke of burning waste. The purpose of writing this article is to build public awareness of the importance of maintaining environmental health, especially regarding the impact of smoke from burning garbage; provide knowledge as well as a demonstration of the Smokeless Burn Barrel tool as an alternative solution to minimize smoke from burning garbage using the Smokeless Burn Barrel; and find out about the difference between burning garbage in general by the community and the combustion process using the Smokeless Burn Barrel tool. The method that can be done is by conducting socialization and demonstration using the Smokeless Burn Barrel tool. The results that can be obtained show that the community knows about the impact of smoke from burning waste; knows the Smokeless Burn Barrel tool directly as an alternative solution to minimize smoke from burning waste; and knows the difference between burning waste in general by the community and the combustion process using the Smokeless Burn Barrel tool.